Relaxation of Polyvinyl Butyral Film with Non-uniform Thickness - Mareska, Ales; Kordova, Tereza; Havlik Mika, Martin (Manufacturing Technology Journal, 2022)
Polyvinyl butyral is a material that is widely used in the manufacture of laminated glass sheets. Polyvinyl butyral film is widely used as an intermediate layer for laminated automotive or architectural glass. The intermediate layer primarily ensures the safety function of the laminated glass. Other advantages of laminated glass with a polyvinyl butyral interlayer include that it can be adapted to perform other functions, including acoustic functions, anti-reflection functions or functions enabling information to be projected on the glass with this interlayer. In this work, the influence of further processing of polyvinyl butyral film with non-uniform thickness is studied. Further processing may have a negative impact to the profile of PVB material.
Keywords: Technology; Automotive; Glass; Performance; PVB